Moving object detection at night - Chew, Chin Lee (2007)
Detection of moving object in during day light has been an active research areas and variety of well established algorithms have been proposed. However, the detection moving objects during night time has not yet received equal attention as the detection during the day time. There can be two important reasons for this. Firstly, because of the absent of light, the object does not appear to be visible and hence the camera or capturing device used for the day light would not able to capture this object during night time. Secondly, the method proposed during day light does not work during night time since the surrounding situation is different. During night time, moving vehicle for example will have its lights on that will enlighten its surrounding. This bright area will also change as the vehicle moves and as a result this will affect the image differencing operation. To avoid this false moving object, different approach has to be developed. A technique that this project will look at is to consider only dense bright regions that correspond to the vehicle’s lights only. Depending on the angle of the camera, the distance between lights of the car will maintain so as for other vehicles. In addition, different distance value can be used to classify the type of moving vehicle i.e. either it’s a car, lorry, or motorcycle. As such, this project will a software-based project. A video sequence captured from infrared sensitive camera for night vision application will be utilized.